Optimalisasi Ketahanan Energi Melalui Kebijakan Pengurangan Konsumsi Gas Elpiji di Indonesia - Ronald Sianipar (Universitas Serang Raya, 2023)
This article aims to analyze energy security policies in Indonesia related to reducing the use of fossil energy by increasing the use of renewable energy. The problem is focused on the idea of the Government of Indonesia to switch the use of Liquefied Petroleum Gas (LPG) based energy to electricity-based energy, especially for household consumers. To approach this problem, theoretical references from scarcity and energy security theories are used, related to current LPG-based energy management in Indonesia and plans for the future. The data were collected through secondary data, literature review, and field studies and were analyzed qualitatively. The results of this study indicate that renewable energy used as a basis for electrical energy is expected to reduce dependence on fossil energy, namely LPG gas. The policy accompanying this energy transition uses a price ceiling policy on LPG gas and an alternative LPG policy. Government policy emphasizes the ceiling price, which sets the highest retail price (HET) for LPG gas. This alternative policy is supported by the use of electricity from renewable energy, including water, wind, biomass, and solar. Another energy alternative is new energy, namely dimethyl ether (DME), which is obtained from processed coal with low calories. In terms of implementation, to maintain a stable supply in the market, it is necessary to monitor and evaluate so that The Gass can still maintain the gas supply and It can control the energy demand for households.